Interrelation among different instability indices of the troposphere over Dhaka associated with thunderstorms/nor'westers over Bangladesh during the pre-monsoon season (MAUSAM, 2007)
Attempts have been made to correlate different instability indices among themselves statistically. The study reveals that the Showalter Stability Index (SI) has moderate to good correlations with different instability indices except Dew-point Index (DPI), Vertical Total Index (VT), Modified Vertical Total Index (MVT) and Modified K-Index (MK). Most of the correlations co-efficient are found to be significant up to 99% level of significance except Dry Instability Index (DII), which has correlation with SI up to 95% level of significance. Lifted Index (LI) has moderate to good correlation with different instability indices except DII, K-Index (KI) and MVT. Most of the correlations co-efficient are significant up to 99% level of significance except VT, SWEAT Index (SWI) and MKI, which have correlation with LI up to 95% level of significance. Unmodified instability indices have moderate to strong correlation with the corresponding modified instability indices, having 99% level of significance. The correlation co-efficient of VT and MVT, SWI and Modified SWEAT Index (MSWI), and KI and MKI are comparatively large. Standard errors of estimate are small in almost all the cases except a few. The regression equations obtained are likely to be helpful in the computation of different instability indices.